P06.07.A Natural killer cells lyse glioblastoma stem cells and increase their sensitivity to chemotherapy. (5th September 2022) - Breznik, B; Ko, M; Chen, P; Senjor, E; Majc, B; Novak, M; Habič, A; Jewett, A
Abstract: Background: Glioblastoma is the most common and lethal brain tumor in the adult population and immunotherapy is playing an increasingly central role in the treatment of many cancers. Nevertheless, the search for effective immunotherapeutic approaches for glioblastoma patients continues. In this study, we aimed to explore the therapeutic potential of allogeneic highly activated super-charged natural killer (NK) cells in glioblastoma. Material and Methods: Chromium release- and calcein release-based cytotoxicity assays, ELISA, ELISPOT, and multiplex cytokine assays were used to determine NK cell cytotoxicity against glioblastoma stem cells (GSCs) and secretion of cytokines. Cell surface marker expression using flow cytometry and cell growth in vitro and in vivo were measured to determine GSC phenotype. NK cell killing and penetration in 3D were measured using confocal microscopy of GSC tumorospheres. Results: Super-charged NK cells efficiently lysed patient-derived GSCs in 2D and 3D models potentially reversing the immunosuppression observed in patients. NK-cells secreted IFN-γ, upregulated GSC surface expression of CD54 and MHC class I and increased sensitivity of GSCs to chemotherapeutic drugs. Co-localization of NK cells with GBM cells in perivascular niches in glioblastoma tissues and their direct contact with GSCs in tumorospheres suggests their ability to infiltrate glioblastoma tumors and target GSCs. Conclusion: Allogeneic super-charged NK cells appear to be a potential therapeutic approach for glioblastoma by selectively killing therapy-resistant cancer stem cell population, increasing their immune-related surface markers and enhancing their sensitivity to chemotherapy. Due to GSC heterogeneity and plasticity personalized immunotherapeutic strategies should be developed to effectively target glioblastomas.